2011
DOI: 10.1007/s10565-011-9183-9
|View full text |Cite
|
Sign up to set email alerts
|

Mineral fibre toxicity: expression of retinoblastoma (Rb) and phospho-retinoblastoma (pRb) protein in alveolar epithelial and mesothelial cell lines exposed to fluoro-edenite fibres

Abstract: Several asbestos-like mineral fibres, including fluoro-edenite, may cause lung cancer and/or other lung diseases. However, biological and molecular mechanisms linked to cancer development after mineral fibre exposure have not been fully investigated. In the present study, human non-malignant mesothelial (MeT-5A) and human bronchoalveolar alveolar epithelial (A549) cell lines were incubated with rising concentrations of fluoro-edenite to evaluate the expression of retinoblastoma (Rb) protein, which has been dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…The lung specimens were homogenized in a buffer containing T-Per buffer (Thermoscientific, Rockford, IL, USA) and a protease inhibitor cocktail (Roche Diagnostics) in a Teflon-glass homogenizer followed by sonication. Protein concentrations were determined using Bradford's method [23] using bovine serum albumin as a standard. Sample proteins (50 μg) were diluted in sodium dodecyl sulphate protein gel loading solution (Invitrogen, Monza, Italy), boiled for 5 min, separated on 4%-12% Bistris gel (Invitrogen) and electroblotted onto nitrocellulose membranes (Invitrogen).…”
Section: Western Blotmentioning
confidence: 99%
“…The lung specimens were homogenized in a buffer containing T-Per buffer (Thermoscientific, Rockford, IL, USA) and a protease inhibitor cocktail (Roche Diagnostics) in a Teflon-glass homogenizer followed by sonication. Protein concentrations were determined using Bradford's method [23] using bovine serum albumin as a standard. Sample proteins (50 μg) were diluted in sodium dodecyl sulphate protein gel loading solution (Invitrogen, Monza, Italy), boiled for 5 min, separated on 4%-12% Bistris gel (Invitrogen) and electroblotted onto nitrocellulose membranes (Invitrogen).…”
Section: Western Blotmentioning
confidence: 99%
“…Such an activation may induce specific B-cell clones to proliferate as a consequence of the chronic antigenic stimulation sustained by different infectious agents ( 23 , 24 ). Moreover, the involvement of the tumor microenvironment along with cytokine release may be associated with tumor development in workers exposed to asbestos or to other fibers ( 25 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such chronic inflammation is associated with the production of several cytokines and growth factors that may cause cellular proliferation and apoptosis arrest (9,22). On this matter, it has been shown that p27 is downregulated in mesothelial cells following exposure to FE fibers (23). Notably, p27 is considered a tumor suppressor gene due to its function as a regulator of the cell cycle, and in cancers it is often inactivated (24).…”
Section: Discussionmentioning
confidence: 99%